State and Protection of Cultural Heritage in Bone, South Sulawesi: Perspectives on National Law and Islamic Law - Sugirman, Andi; Latif, Hamzah; Darna, Andi; Rizwan, Muhammad; Nawawi, Jumriani (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Indonesia possesses a rich cultural heritage consisting of both tangible and intangible artifacts that continue to exist in the present day. This cultural heritage has significantly contributed to the advancement of human civilization, encompassing economic, social, and scientific dimensions. This study seeks to examine the state's involvement in safeguarding cultural assets in Bone Regency, located in South Sulawesi, Indonesia. The article employs an empirical research methodology that applies both the constitutional law and the Islamic law. Data were gathered by comprehensive interviews, direct observation, and the collection of relevant documents. The sources for the study included the tourism office, members of the People's Representative Council (DPR), as well as religious and community leaders. The investigated papers consisted of legal regulations, including laws, regulations, and relevant journal articles. The findings indicate that the government plays a crucial role in the protection of the cultural assets in Bone Regency. Within the realm of the constitutional law, the government has enacted Law No. 11 of 2010, which pertains to Cultural Heritage. Similarly, the Bone Regency government has also enacted Regional Regulation No. 7 of 2020, which concerns the Preservation and Management of Cultural Heritage. To enforce this protection, many cultural legacies have been designated, such as the burial grounds of the Bone monarchs and significant cultural and historical locations. Within the framework of the Islamic law, the preservation of cultural assets is considered advantageous. The advantages derived from cultural heritage include the reinforcement of national identity and character, historical education, the promotion of tourism attractions, and the provision of a religious lesson for present and future generations.